Modeling Landslides Catastrophe for Risk Analysis and Management in Chittagong City of Bangladesh - Biswas, Rathindra Nath; Lasker, Mohammad Sujoun (The Jahangirnagar Review, 2024)
This study was carried out for inventory mapping, landslide-occurring mechanisms, bio-physical risk analysis, and proper mitigation strategies. Therefore, the causal mechanism of the landslide catastrophe was assessed by the DPSIR model framework. Accordingly, technological, structural, and non-structural management models are also applied for landslide catastrophe mitigation in the vulnerable zones of the study area. Technological management models focused on early warning and raising awareness through various communication devices; structural management models prevented structural development and enhanced hilly areas with a green-ecological approach; and non-structural management models included settlement, land use, building code. To accomplished the research goal, both qualitative and quantitative analyses were applied using primary and secondary sources of data. Moreover, GIS cartographic tools and techniques were used for risk mapping, considering the geological, geomorphological, topographical, hydrometrological, and anthropogenic aspects of the study area. Analysis results demonstrated that the probability of catastrophic landslides occurring (67.27%) was far higher than the probability of other hazards, including flooding (0.15%), earthquakes (6.57%), tropical cyclones (0.84%), and waterlogging (25.17%). The findings of the research will help disaster management specialists, environmentalists, urban planners, and decision-makers in mitigation approaches to landslide catastrophes in the study area.